Health psychology in Ghana: A review of the multidisciplinary origins of a young sub-field and its future prospects - De-Graft Aikins, A. (Journal of Health Psychology, 2018)
This article presents a historical overview of psychology applied to health and health psychology in Ghana. A brief history of health, illness and healthcare in Ghana is introduced. Then, the history of psychology in Ghana is presented, with signposts of the major turns in the field in relation to psychology and other disciplines applied to health and the emergence of health psychology as a sub-field. Selected health psychology studies are reviewed to highlight ideological trends in the field. Finally, future prospects are considered in terms of how the sub-field can transition into an established critical field with unique contributions to make to global health psychology.
Keywords: Anthropology; Clinical psychology; Critical health psychology; Ghana; Health policy